Tax Aggressiveness In Property And Real Estate Companies: The Role Of Financial Distress And Transfer Pricing - Putri, Rizma Fatmawati; Akbar, Fajar Syaiful (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research aims to examine the impact of financial distress and transfer pricing on tax aggressiveness among property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2021to 2023. Methodology: Using a quantitative approach, 32 companies were selected via purposive sampling. Tax aggressiveness was measured using ABTD, financial distress with the Altman Z-Score, and transfer pricing via the Related Party Transaction (RPT) ratio. Multiple linear regression was performed using SPSS. Results: The results indicate that financial distress signfificantly increase tax aggressiveness (β= 0,124, p<0,05), while transfer pricing has a negative but statiscally insignificant effect (β= -0,139, p>0,05). Findings: Firms under financial pressure tend to adopt more aggressive tax strategies. The use of transfer pricing does not directly influence tax behavior, posibly due to adherence to the arm’s length principle. Novelty & Originality: This research provides sector-specific empirical evidence of tax aggressiveness mechanisms in emerging economies, offering new insight into tax compliance behavior and signaling theory. Conclusion: Financial distress is a key determinant of aggressive tax practices. Policymakers sholud consider firm-specific conditions when designing tax regulations. Type of Paper: Quantitative empirical research.